The System of Values of the Monotheistic Druze Managers from Israel Based on the Schwartz Theory of Human Basic Values - Radwan MANSOUR; Nicolae BIBU (Revista de Management Comparat International)
This article is discussing the values that are specific to managers belonging to the Druze community from Israel. The Druze community is an ethnic community having some very unique characteristics, possessing an identity based on a mystic emotional connection which originates from heart and soul, a cross-border connection that brings together the ancient past, the present and the future without territorial identity. When the value system is understood and accepted by the organizational members and managers, they are committed to it and bear responsibility for their actions. Therefore, there is integration, dialogue, nourishment and balance between the particular desires for responsibility and the commitment to the organization.